2011
DOI: 10.1504/ijbpim.2011.043391
|View full text |Cite
|
Sign up to set email alerts
|

DYPROTO â tools for dynamic business processes

Abstract: Abstract:In this article, we present research results about tools for supporting dynamic business processes. This research work has been conducted in a three-year cooperation between our department and an IT service provider for insurance companies. Our partner's process management system (PMS) is rather aligned with static processes, whose structure is not changed at process run time. Therefore, we contribute an approach for obtaining dynamic process execution support based on this static PMS by automatically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…• A7 = DYPROTO, (Wörzberger and Heer, 2011;Heer et al, 2009), where implementation includes prototype, without examples, • A8 = RoDP, (Hu et al, 2013), where implementation includes example with Mathlab simulation experiment, • A9 = BPFAMA (Boukhebouze et al, 2011), where implementation includes prototype, print screens and example of purchase order, • A10, (Mejia Bernal et al, 2010), where implementation includes case study with examples, • A11 = Our proposed approach, where implementation includes prototype and print screens.…”
Section: Main Results and Discussionmentioning
confidence: 99%
“…• A7 = DYPROTO, (Wörzberger and Heer, 2011;Heer et al, 2009), where implementation includes prototype, without examples, • A8 = RoDP, (Hu et al, 2013), where implementation includes example with Mathlab simulation experiment, • A9 = BPFAMA (Boukhebouze et al, 2011), where implementation includes prototype, print screens and example of purchase order, • A10, (Mejia Bernal et al, 2010), where implementation includes case study with examples, • A11 = Our proposed approach, where implementation includes prototype and print screens.…”
Section: Main Results and Discussionmentioning
confidence: 99%
“…The analysis showed that dynamic business processes are not understood and defined similar so other authors proposed dynamic model implementation solutions which we divided into two examined problems: changing business processes at runtime [1], [2], [4], [5], [10], [11] or executing business process with no predefined sequence of activities [7], [12]. In this section we provide realization for a different solution, which proposed by different authors.…”
Section: Model Implementation Solutionsmentioning
confidence: 99%
“…The tool has been developed on the ground of submitted Weber dynamic model. However the main attention is to solve the correctness of problems which arise due to the dynamics [10].…”
Section: Model Implementation Solutionsmentioning
confidence: 99%
“…The system uses aspect-oriented approach, so it can modify functionality at runtime. Wörzberger, Heer (2011) provided DYPROTO tool, which can insert new activities, delete old activities or dynamically implement activity. Weber et al (2008) provided an overview over different aspects of flexibility in workflow management (WFM) systems and defined the change patterns used in WFM systems.…”
Section: Introductionmentioning
confidence: 99%